Point-to-point Coulomb effects in high brightness photoelectron beam lines for ultrafast electron diffraction - M. Gordon (Physical Review Accelerators and Beams, 2021)
In an effort to increase spatial and temporal resolution of ultrafast electron diffraction and microscopy, ultrahigh-brightness photocathodes are actively sought to improve electron beam quality. Beam dynamics codes often approximate the Coulomb interaction with mean-field space charge, which is a good approximation in traditional beams. However, point-to-point Coulomb effects, such as disorder-induced heating (DIH) and the Boersch effect, cannot be neglected in cold, dense beams produced by such photocathodes. In this paper, we introduce two new numerical methods to calculate the important effects of the photocathode image charge when using a point-to-point interaction model. Equipped with an accurate model of the image charge, we calculate the effects of point-to-point interactions on two high-brightness photoemission beam lines for ultrafast diffraction. The first beam line uses a 200 keV gun, whereas the second uses a 5 meV gun, each operating in the single-shot diffraction regime with 10^{5}  electrons/pulse. For the beam lines simulated in this paper, assuming a zero photoemission temperature, it is shown that including stochastic Coulomb effects increases the final emittance by over a factor of 2 and decreases the peak transverse phase space density by over a factor of 3 as compared to mean-field simulations. We then introduce a method to compute the energy released by DIH using the pair correlation function and approximate the contribution DIH has on the emittance, which may serve as a reasonable estimate for the effects of DIH beyond the cases studied in this work. This DIH energy was found to scale very near the theoretical result for stationary ultracold plasmas, and it accounts for over half of the emittance growth above mean-field simulations.